2023
DOI: 10.1002/adfm.202309666
|View full text |Cite
|
Sign up to set email alerts
|

Bi‐Directional Electrolytic Reduction of CO2 to Mesoporous Carbons with Regulated Structure and Surface Functional Groups for Zn‐ion Capacitors

Ao Yu,
Yinan Zhao,
Wei Zhang
et al.

Abstract: Zn‐ion capacitors (ZICs) take advantage of batteries and supercapacitors in delivering high energy and power densities for energy storage by using porous carbons due to their low cost, lightweight, high conductivity, and good stability. However, it remains a grand challenge to regulate the mesoporous structures of carbons, including pore sizes and surface functional groups, which are essential for ion transport and electrochemical reactions of ZICs. Herein, a bi‐directional electrolysis strategy is developed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…59,60 This enhancement occurs through the following reactions: C 61,62 Although the oxygen-containing carbons have many advantages for ZICs, only a few works about the CO 2 -C were reported. 15,63 Li and Yang et al reported a CO 2 -derived OMC for ZICs. 15 OMC was innovatively obtained through bidirectional electrolytic reduction of CO 2 in a molten Li 2 CO 3 −Na 2 CO 3 −K 2 CO 3 .…”
Section: Capacitorsmentioning
confidence: 99%
See 3 more Smart Citations
“…59,60 This enhancement occurs through the following reactions: C 61,62 Although the oxygen-containing carbons have many advantages for ZICs, only a few works about the CO 2 -C were reported. 15,63 Li and Yang et al reported a CO 2 -derived OMC for ZICs. 15 OMC was innovatively obtained through bidirectional electrolytic reduction of CO 2 in a molten Li 2 CO 3 −Na 2 CO 3 −K 2 CO 3 .…”
Section: Capacitorsmentioning
confidence: 99%
“…15,63 Li and Yang et al reported a CO 2 -derived OMC for ZICs. 15 OMC was innovatively obtained through bidirectional electrolytic reduction of CO 2 in a molten Li 2 CO 3 −Na 2 CO 3 −K 2 CO 3 . As illustrated in Figure 3a, CO 2 is initially reduced to solid carbon on the steel cathode.…”
Section: Capacitorsmentioning
confidence: 99%
See 2 more Smart Citations